Pengembangan Modul untuk Guru dalam Meningkatkan Self Efficacy Sains Siswa SMA - Melly Sanjaya; Lena N. Panjaitan; Listyo Yuwanto (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
Students often interpret science lessons as more difficult lessons compared to other subjects because these subjects require more learning effort and when students lose their desire to follow science subjects, they tend to perceive less ability in the field of science, this can have an impact on unsatisfactory student learning outcomes. Self-efficacy is the strongest predictor of academic achievement, because self-efficacy influences behavioural choices, namely choosing the field to be mastered, determining how much effort is exerted and influencing thought patterns and emotional reactions. Self-efficacy can be grown and learned. Therefore, the teacher's role is very important in increasing student self-efficacy. This study was conducted to find out the description of the self-efficacy of high school students towards science lessons, the factors that cause science high school students to have low self-efficacy, what efforts have been made and what efforts have not been made by teachers to overcome the problems of students who have low science self-efficacy. Based on the results of data collection, a module for teachers was compiled which aims to increase students' self-efficacy towards science lessons.